The impact of female employment on male wages and careers: Evidence from the English banking industry, 1890 - 1941 - Andrew Seltzer (Institute for the Study of Labor (IZA), 2012)
The late 19th and early 20th century British labour market experienced an influx of female clerical workers. Employers argued that female employment increased opportunities for men to advance; however, most male clerks regarded this expansion of the labour supply as a threat to their pay and status. This paper examines the effects of female employment on male clerks using data from Williams Deacon's Bank covering a period 25 years prior and 25 years subsequent to the initial employment of women. It is shown that within position women were substitutes for men, although the degree of substitutability was less for older men than for juniors. In addition, the employment of women in routine positions allowed the Bank to expand its branch network, creating new higher-level positions, which were almost always filled by men.
Keywords: N3; J3; 330; clerical labour markets; female employment; spill over effects; internal labour markets; Büroberufe; Bankberufe; Weibliche Arbeitskräfte; Interner Arbeitsmarkt; Männer; Lohn; Erwerbsverlauf; Großbritannien